2020
DOI: 10.1002/bjs.11520
|View full text |Cite
|
Sign up to set email alerts
|

Perianal block with ropivacaine as a supplement to anaesthesia in proctological surgery: double-blind randomized placebo-controlled trial (PERCEPT)

Abstract: Background The benefit of a perianal block as an adjunct to general or regional anaesthesia is debated. This RCT aimed to compare pain at 24 h and up to 14 days after proctological surgery in patients with and without a perianal block. Methods Between January 2018 and April 2019, patients were allocated to receive a perianal block with ropivacaine or placebo as an adjunct to anaesthesia. Patients, surgeons and assessors were blinded. The primary outcome was pain measured on a numerical rating scale (NRS) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
8
0
3
Order By: Relevance
“…Taken together, TPVB might reduce the occurrence of EA possibly by alleviating the acute post-operative pain. Previous studies showed that regional nerve blockade not only enhances post-operative analgesia but also produces a higher quality of recovery after surgery (23)(24)(25). This study found that patients receiving TPVB had a shorter emergence and extubation time than those with ICNBs.…”
Section: Discussionsupporting
confidence: 49%
“…Taken together, TPVB might reduce the occurrence of EA possibly by alleviating the acute post-operative pain. Previous studies showed that regional nerve blockade not only enhances post-operative analgesia but also produces a higher quality of recovery after surgery (23)(24)(25). This study found that patients receiving TPVB had a shorter emergence and extubation time than those with ICNBs.…”
Section: Discussionsupporting
confidence: 49%
“…A previous study reports more than 70% of patients had severe 24 hours postoperative pain where the degree of the pain is twice that of cholecystectomy and appendectomy procedures. 1,2 In addition, abiding and concerning the level of postoperative pain is associated with a prolonged recovery period. Anus has abundant sensory innervation and is more susceptible to pain.…”
Section: Introductionmentioning
confidence: 99%
“…Επιπρόσθετα, αν και εφαρμόζεται εκτενώς σε επεμβάσεις 'μιας ημέρας', η ραχιαία αναισθησία παρουσιάζει ένα αξιοσημείωτο προφίλ περιεγχειρητικών ανεπιθύμητων ενεργειών, οι οποίες αποτρέπουν την έγκαιρη ανάρρωση και μειώνουν τη συνολική ποιότητα ζωής των ασθενών (QoL) [159][160][161][162][163][164]. Αντιθέτως η εφαρμογή του αποκλεισμού του αιδοιϊκού νεύρου, ως αποκλειστική ή συμπληρωματική τεχνική αναισθησίας έχει επιδείξει αρκετά υποσχόμενα αποτελέσματα [165][166][167]. Ο αποκλεισμός του αιδοιϊκού νεύρου, αποτελεί μια πιο στοχευμένη και ελάχιστα επεμβατική τεχνική αναισθησίας, που σε σύγκριση με την καθιερωμένη ραχιαία αναισθησία, παρουσιάζει μια επαυξημένη και παρατεταμένη αναισθητική δράση [131,165,167,168].…”
Section: αιτιολόγησηunclassified
“…Η αιτιολογία των διαταραχών ούρησης περιλαμβάνει έναν συνδυασμό οδών, όπως συμπαθητικό αντανακλαστικό ουρηθρικό σπασμό έπειτα από πρωκτική διαστολή και αποκλεισμό των απαγωγών νεύρων από την ραχιαία αναισθησία[131,185]. Η επίδραση του τελευταίου παράγοντα έχει επιβεβαιωθεί σε πολλές σειρές ασθενών[132,160,[164][165][166][167]176]. Αντιθέτως, ο εκλεκτικός αποκλεισμός του αιδοιϊκού νεύρου δεν επηρεάζει την νεύρωση της ουροδόχου κύστης ή των σφιγκτήρων, επιτρέποντας, έτσι, την ανεμπόδιστη ούρηση[132,160,[164][165][166][167]176].…”
unclassified
See 1 more Smart Citation